Evaluation of health and safety management systemAccording to international standards OHSAS 18001: 2007A case study at Al-Mamoun Factory / General Company for vegetable oil industry - محمد, زهرة عبد (Journal of Economics and Administrative Sciences, 2009)
This research aims to knowledge of the scope of applying the international specification of which is regarded to occupational health and safety management system (OHSAS 18001) second edition for year 2007 by The AL-Mammon Factory / The General Company For Vegetable Oils Industry in order to diagnosis the gap between specification requirements and reality by using the checklist made based upon the items of the specification, after translating the English copy into Arabic. The results of the research and analysis that occupational health and safety management system in comparison to the specification requirements in all of its main items, which was (%22.26) applied and documented partly, this refer to the existence of great gap (%77.74) in attaining occupational health and safety management system requirements.